BENTUK UMUM PENENTUAN INVERS MATRIKS DENGAN METODE COUNTER - Abidin, Wahyuni; Nurfalaq (Universitas Islam Negeri Alauddin Makassar, 2013)
This thesis discusses the general form of the method of determining the inverse matrix counter. The purpose of this research is to determine the general solution in the form of theinverse matrix by using counters and to compare the results obtained in finding the inverse matrix manually using Matlab program. The method used in this thesis is a method ofcounters. By using the above method is obtained in the form of a general settlement to find the inverse matrix